Shallow gas accumulations in the German North Sea. (March 2018) - Müller, Simon; Reinhardt, Lutz; Franke, Dieter; Gaedicke, Christoph; Winsemann, Jutta
Abstract: Shallow gas, here defined as free gas that is trapped in unconsolidated, deltaic and shallow marine siliciclastic sediments of Plio-Pleistocene age, is found within the topmost 1000 m of sediment in the southern North Sea. Shallow amplitude anomalies in seismic reflection data are likely due to the presence of gas. The most prominent and easy-to-recognize indicators are high-amplitude anomalies, or "bright spots", that are widespread within the southern North Sea. Gas from shallow reservoirs is currently produced offshore The Netherlands. In this study, we determine whether there are analogous shallow gas accumulations within the German North Sea. Therefore, we screened 2D and 3D multichannel seismic data for shallow amplitude anomalies. Several clusters of bright spots are identified above salt domes that closely resemble the economic deposits known in the Dutch sector in both size and their characteristic multilayered shape. Three of these potential gas accumulations, occurring in combination with additional hydrocarbon indicators such as seismic attenuation and velocity push-downs, are investigated in detail and compared to shallow gas fields from offshore The Netherlands. Amplitude anomalies indicate gas seepage on the seafloor that may contribute to the atmospheric methane budget and may have an impact on offshore infrastructure. Graphical abstract: Image 1 Highlights: Mapping of stacked shallow gas accumulations in the German North Sea. Seismic characterisation of three potential shallow gas accumulations. Integration into a seismic-stratigraphic framework for the German North Sea. Comparison with producing shallow gas fields from offshore The Netherlands.